Babies for Bling: Are teenage girls having children to access grants? - Hodes, R; Toska, E; Gittings, L (Southern African HIV Clinicians Society, 2016)
This is a story that is often told: a young woman from a poor family has had a baby so that she can access the child support grant. Then, instead of spending the money on her family, she dumps the baby with her mother or aunt. She uses the grant to buy trendy clothes, beauty treatments and booze. The state has provided this young mother with money to care for her child, but she is wasting it on selfish luxuries. Among nurses and social workers, alarm about the misuse of social grants is growing. For many health and social workers, it appears that young people are increasingly using grants for income, as a substitute for formal employment.